Show your solution

d) (2x3y2z) (3xyz2)=

e) 40x⁴y⁶
÷ 8x⁶y⁴=

f) 6(x⁴y⁶)
÷12x⁴x⁵=​


Sagot :

Answer:

d)6x⁴y³z³

e) 5y²/x²

f) y⁶/2x⁵

Step-by-step explanation:

NOTE: Im assuming that in d), the 3 & second 2 in the first factor and the 2 in the second factor are exponents.

Learning Competencies:

  1. Dividing Polynomials with Exponents
  2. Multiplying Polynomials with Exponents

d) (2x³y²z)(3xyz²) = 2•3 [x^(3+1)] [y^(2+1)] [z^(1+2)]

= 6x⁴y³z³

e) 40x⁴y⁶÷8x⁶y⁴= 40/8 [x^(4-6)] [y^(6-4)]

5(x^-2)y²

=5y²/x²

f) 6x⁴y⁶÷12x⁴x⁵= 6/12 {[x^[4-(4+5)]} (y⁶)

1/2 (x^-5)(y⁶)

=y⁶/2x⁵